Myositis-specific Autoantibodies Reacting to Both Tif1gamma and Mi-2 in a Patient with Juvenile Dermatomyositis - Daiki Takezaki; Shuhei Onishi; Yasuhito Hamaguchi; Manabu Fujimoto; Hiroko Kohzan; Toshihisa Hamada (Medical Journals Sweden, 2020)
Abstract is missing (Short communication)